Realms of light : the Baroque - Marner, Eugene; Satrina, Carole Lucia (Art of the Western world / executivr producer, Perry Miller Adato, 1989)
Examines the divergent themes of the baroque period, including a new emotional appeal as seen in Bernini's The Ecstacy of St. Teresa, Caravaggio's naturalism, Velasquez's multi layered works, and the irse of bourgeois values as seen in Rembrandt's works.